A Plasmopara viticola RXLR effector targets a chloroplast protein PsbP to inhibit ROS production in grapevine. (24th April 2021) - Liu, Ruiqi; Chen, Tingting; Yin, Xiao; Xiang, Gaoqing; Peng, Jing; Fu, Qingqing; Li, Mengyuan; Shang, Boxing; Ma, Hui; Liu, Guotian; Wang, Yuejin; Xu, Yan
SUMMARY: Pathogens secrete a large number of effectors that manipulate host processes to create an environment conducive to pathogen colonization. However, the underlying mechanisms by which Plasmopara viticola effectors manipulate host plant cells remain largely unclear. In this study, we reported that RXLR31154, a P. viticola RXLR effector, was highly expressed during the early stages of P. viticola infection. In our study, stable expression of RXLR31154 in grapevine ( Vitis vinifera ) and Nicotiana benthamiana promoted leaf colonization by P . viticola and Phytophthora capsici, respectively. By yeast two‐hybrid screening, the 23‐kDa oxygen‐evolving enhancer 2 (VpOEE2 or VpPsbP), encoded by the PsbP gene, in V itis piasezkii accession Liuba‐8 was identified as a host target of RXLR31154. Overexpression of VpPsbP enhanced susceptibility to P. viticola in grapevine and P. capsici in N. benthamiana, and silencing of NbPsbPs, the homologs of PsbP in N. benthamiana, reduced P. capcisi colonization, indicating that PsbP is a susceptibility factor. RXLR31154 and VpPsbP protein were co‐localized in the chloroplast. Moreover, VpPsbP reduced H2 O2 accumulation and activated the 1 O2 signaling pathway in grapevine. RXLR31154 could stabilize PsbP. Together, our data revealed that RXLR31154 reduces H2 O2 accumulation and activates the 1 O2 signaling pathway through stabilizing PsbP, thereby promoting disease. Significance Statement: Downy mildew, caused by Plasmopara viticola, is a major threat to grapevine ( Vitis vinifera ) growth and development. Most table grapes and wine grapes are susceptible to downy mildew. Pathogens secrete many effectors that manipulate host processes to facilitate pathogen colonization. Here, we identified an RXLR effector from P . viticola, RXLR31154, which participated in ROS‐mediated immunity by targeting PsbP, thereby promoting disease. Understanding the molecular dialogs between P. viticola and grapevine is instrumental for sustaining effective disease control. ​